Cover Feature: cis‐On/trans‐Off of DNA Hybridization with Alkylthio‐azobenzene on L‐Threoninol Responding to Visible Light (ChemPhotoChem 6/2019). Issue 6 (11th June 2019) - Asanuma, Hiroyuki; Ishikawa, Teruchika; Yamano, Yuuhei; Murayama, Keiji; Liang, Xingguo
Abstract : The Cover Feature illustrates photoregulation of the formation and dissociation of hybridization by photoresponsive DNA, in which alkylthioazobenzenes are tethered on an L‐threoninol scaffold. By irradiating with λ=400 nm light, the DNA duplex is formed in the cis form while it is dissociated in the trans form upon irradiation with 520 nm light. More information can be found in the Article by H. Asanuma et al. on page 418 in Issue 6, 2019 (DOI: 10.1002/cptc.201900060 ).